Utilization of Breast Cancer Screening in Brazil: An External Assessment of Primary Health Care Access and Quality Improvement Program - Mara Rejane Barroso Barcelos; Bruno Pereira Nunes; Suele Manjourany Silva Duro; Elaine Tomasi; Rita de Cássia Duarte Lima; Malgorzata Nabialczyk Chalupowski; Timothy Richard Rebbeck; Luiz Augusto Facchini (Taylor & Francis Group, 2018)
Breast cancer is the most frequent type of cancer in women and the second leading cause of cancer death after lung cancer in more developed countries and the leading cause of death in developing countries. The aim of this study was to analyze the association between three sets of variables and the utilization of breast cancer screening among women attending primary health care centers participating in the Primary Care Access and Quality Improvement Program in Brazil. A survey of 65,391 women was conducted across Brazil in 2012. The primary outcomes were percentage of women who never had a clinical breast examination and percentage of women who never had a mammography. Crude and adjusted analyses performed using Poisson regression assessed the association of these outcomes with service organization variables, as well as with socioeconomic and demographic variables. Results showed that 37.7% of women never had a clinical breast examination and 30.3% never had a mammography. Never having had both screening procedures decreased as the Human Development Index increased. Never having had a clinical breast examination increased with increasing population size and increasing municipal family health strategy coverage. The proportion of women never having had a clinical breast examination was highest in the northern region. White women and those who had a partner had greater utilization of screening. Women who had paid work and lived in families with higher per capita income had greater utilization of clinical breast examination. The proportion of women who never had a mammography was highest for women living in households with six or more people and receiving the Bolsa Família benefit. Women with lower per capita family income had higher utilization of mammography. Appropriate structures and work processes were associated with greater utilization of mammography. Investments in primary health care structure and teamworking processes are essential to improve the utilization of screening, prevention, and early diagnosis of breast cancer in Brazil.